Analisis Kritis terhadap Kesenjangan Hukum dan Praktik Ekonomi Modern : Tinjauan Unsur Maghrib (Maisir, Gharar, dan Riba) - Noerismayanti; Zulfahry Abuhasmy; Dian Novianti; Asriadi Arifin (Al Rikaz: Jurnal Ekonomi Syariah, 2026)
This study aims to analyze the prohibitions in Islamic economic principles, commonly known as MAGHRIB (maisir, gharar, and riba), and their relevance in modern economic practices. The research employs a qualitative approach with a descriptive research design through a library research method. Data were collected from various literature sources, including scientific journals, books, and reports from official institutions relevant to the research topic. The findings indicate that MAGHRIB (maisir, gharar, and riba) constitutes three fundamental concepts in Islamic economics that function to uphold justice, transparency, and economic stability. However, these elements are still widely found in modern economic practices. Riba continues to dominate the global financial system through interest-based mechanisms, gharar appears in digital transactions due to a lack of information transparency, and maisir develops through speculative activities such as trading without proper analysis and online gambling. The prohibition of maisir, gharar, and riba remains highly relevant in addressing the dynamics of the modern economy. Therefore, strengthening literacy, regulatory frameworks, and innovation within the Islamic financial system is essential to create a more equitable, transparent, and sustainable economic system.